A Biosorption of Mercury from Wastewater Using Isolated Aspergillus Sp. Modified 1,10-Phenanthroline: Hill Isotherm Model - Salih, Shameran J.; Anwer, Sewgil S.; Faraj, Rezhna H. (Science Journal of University of Zakho, 2017)
Equilibrium biosorption of mercury (II) onto new developed biosorbent (1,10-phenanthroline-graft- cell/Filamentous fungi) in both free, immobilized and dead cell were investigated. The product was characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). In this work several isotherm models applied to predict the process design for the adsorption system. Hill, Sips, Langmuir and Freundlich utilized to determine the adsorption parameters, the equilibrium data fitted well to Hill and Sips isotherm models followed by Langmuir. Meanwhile, the maximum adsorption capacity proposed by Hill model was 78.67(mg/g) and Sips 78.42(mg/g) were lower than Langmuir models which was 85.16(mg/g). In other hand, the equilibrium data almost fitted to the Freundlich isotherm supporting the postulation of the heterogeneous shape of biosorption to certain range. Hence, On the bases of Langmuir model the biosorption of Hg2+ onto 1,10-phenanthroline-graft- cell/Filamentous was in the favourable area and that confirmed by calculating the separation factor (RL< 1). Nevertheless, new isotherm (Eq. 4) has been derived by the combination of a Langmuir and Freundlich models. The new model agreed well enough (R2 = 0.9863) with the experimental data.